Impact of Changes to Article 42 of the Job Creation Law on Employment Development: Analysis of Constitutional Court Decision Number 168/PUU-XXI/2023 - Mayaka, Raphael (Jurnal Pengembangan Ketenagakerjaan, 2024)
This article analyzes the impact of changes to Article 42 of the Job Creation Law on employment in Indonesia following the Constitutional Court Decision No. 168/PUU-XXI/2023. This change makes it easier for employers to employ foreign workers through the ratification of the utilization plan by the central government. Although it aims to increase the attractiveness of foreign investment and encourage knowledge transfer, this policy poses challenges, such as limited job opportunities for local workers due to low levels of education and skills. The Constitutional Court Decision added a phrase that prioritizes the use of Indonesian workers to improve equal employment opportunities and protect the rights of local workers. This study uses a normative legal method with a statutory and conceptual approach to evaluate the policy. This article recommends improving the skills of local workers through training, education, and strict supervision of policy implementation, so as to create a balance between the need for foreign investment and strengthening national competitiveness.